HUBUNGAN TINGKAT PENGETAHUAN TENTANG ANEMIA PADA STATUS GIZI DAN KADAR HEMOGLOBIN REMAJA PUTRI DI DESA BANTARSARI, BOGOR, JAWA BARAT - Wuryanti, Sri; Asiah, Nur; Marsiati, Himmi (Jurnal Gizi dan Pangan Soedirman, 2024)
Based on Basic Health Research (Riskesdas) in 2018, the prevalence of anemia in adolescent was 32%. Anemia in teenage girls have negative impacts on pregnancy in the future. This study was to find out the knowledge of anemia and nutrition, the percentage of anemia, whether there were relationship between the knowledge about anemia and nutritional status, and the relationship between the knowledge about anemia and hemoglobin levels in teenage girls in Bogor. This research was a cross sectional study. Data were collected by filling out questionnaires, anthropometric measurements and hemoglobine levels. The subjects were female students, 12 to 20 years from 2 schools at Bantarsari Village, Bogor, December 2022. It was found that 25 subjects (22.1%) had poor nutritional status, 23 subjects (20.4%) suffered from anemia and the majority of research subjects had fairly good knowledge (92.9%). In the Bivariate test, a significant relationship was found between the level of knowledge of research subjects and the level of anemia (P = 0.009) and a significant relationship was obtained between the level of knowledge of research subjects and nutritional status (P = 0.003). Therefore it is important to increase the knowledge of teenage girls about anemia.